Determination of Multiclass Pharmaceutical Residues in Milk Using Modified QuEChERS and Liquid-Chromatography-Hybrid Linear Ion Trap/Orbitrap Mass Spectrometry: Comparison of Clean-Up Approaches and Validation Studies - Ourania Koloka; Marioanna Koulama; Dimitra Hela; Triantafyllos Albanis; Ioannis Konstantinou (Molecules, 2023)
A multi-residue method was developed to identify and quantify pharmaceutical drug residues in full-fat milk, using a modified QuEChERS extraction procedure and sonication combined with Ultra-High-Performance Liquid Chromatography–High-Resolution Orbitrap Mass Spectrometry (UHPLC-HR-Orbitrap-MS). Sample preparation involves three different QuEChERS extraction procedures and sorbents for the purification step. The optimized modified extraction method, combined with the clean-up approaches using C18 and the EMR-Lipid sorbent, has been validated in terms of linearity, recovery, precision, LOD and LOQ, matrix effects (ME) and expanded uncertainty. The optimized method showed a linearity >0.9903, recoveries within the range 65.1–120.1%, precision (expressed as %RSD) <17.5%, medium (<39.9%) to low (<16.7%) matrix effects and acceptable expanded uncertainty (<33.1%). Finally, the proposed method was applied to representative real samples of milk (by local markets), revealing the existence of one pharmaceutical drug (imidocarb) in one sample.